Quality improvement using lean six sigma in air conditioning products - Purwanto, Cipto; Jayanti, Brian Sila; Bernard, Fransiska Sekarlati; Ekawati, Ardhianiswari Diah (Jurnal Polimesin, 2024)
Air Conditioners (AC) are essential electronic products for residential and industrial buildings in tropical countries or during warm weather in general. The penetration ratio of electronic Air Conditioners (AC) has been increasing every year. Data collection and processing were conducted directly by the author through observation, measurement, and calculation on the heat exchanger production of Air Conditioners (AC). In the production cost of Air Conditioners (AC), the heat exchanger accounts for the second highest cost after the compressor making up 19% of the total cost. The high cost is caused by pipe leaks, with a percentage of 73.7%. This research aims to analyze the improvement of Air Conditioner (AC) production quality using the Six Sigma method. The defect rate in the heat exchanger, evaluated through the Define, Measure, Analyze, Improve, Control (DMAIC) method originating from Six Sigma, was found to be 1,144.8 defects per million opportunities. Further analysis was conducted with the Failure Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) methods. This research was conducted at XYZ company by conducting interviews and observations for 3 months. FMEA and FTA analysis resulted in the top two failure risks based on the Risk Priority Number (RPN): flaring diameter too big and unstable brazing skill. In the manual brazing process, it was found that work by operators with level A certification produced 9% below standard outcomes. An improvement was obtained by changing the punch flaring size to 8.5mm and conducting skill certification and training for brazing operators. The results of the proposed improvement implementation led to a reduction in the DPMO value to 403.35, equivalent to a decrease of 64.7%. The defect ratio in production decreased by 38.1%, exceeding the previous target of 26.2%, equivalent to $31.96/month/unit. The results of this study are horizontal, allowing the implementation of improvements made in the heat exchanger production process to be expanded to other cooling electronic production processes.